Child Marriage Prevention Strategy in the Regional Development Planning Board of Bone Regency - Anas, Aswar (Al-Bayyinah, 2024)
This research aims to analyze the effectiveness of the Child Marriage Prevention Strategy program implemented by the Regional Development Planning Agency (Bappeda) in preventing child marriage in Bone Regency. The study employs a qualitative descriptive analysis method through a case study in Bone Regency. Data was collected through interviews with Bappeda, the Women Empowerment and Child Protection Agency (DP3AP2KB), the Ministry of Religious Affairs (Kemenag), and the Watampone Class 1A Religious Court. The findings reveal that the implementation of the Child Marriage Prevention Strategy program in Bone Regency involves collaboration among various sectors and stakeholders committed to preventing child marriage. This mechanism encompasses several steps, including coordination meetings with various stakeholders, and monitoring, and evaluating the implementation and success of programs undertaken by each stakeholder in preventing child marriage in Bone Regency. The effectiveness of the Child Marriage Prevention Strategy program implemented by Bappeda Bone Regency has been proven effective in preventing child marriage, as evidenced by a significant decrease in the number of child marriages and dispensation for marriage cases at the Watampone Class 1A Religious Court in Bone Regency. The Child Marriage Prevention Strategy implemented by Bappeda Bone Regency represents a crucial effort to prevent child marriage, aligning with the principles of Islamic Family Law that prioritize child protection and well-being.